Implementasi Pada Program Bank Sampah Tegeh Sari Lestari Dalam Pengelolaan Sampah Di Kelurahan Tonja Kecamatan Denpasar Utara Kota Denpasar - I Putu Tito Ananda Putra; Ni Wayan Supriliyani; Putu Nomy Yasintha (Business and Investment Review, 2023)
Garbage is a big enough problem in maintaining environmental quality and there are still many people in Indonesia who do not understand waste management properly and independently and with an environmental perspective. Referring to this, the Tegeh Sari Lestari Garbage Bank located in Banjar Tegeh Sari, Tonja Village, North Denpasar District, Denpasar City is a successful pilot model because the Tegeh Sari Lestari Garbage Bank is able to educate the community and is consistent in collecting waste regularly every month. However, in its implementation there are various obstacles, so this study aims to find out how the implementation of the Tegeh Sari Lestari Garbage Bank Program in Waste Management in Tonja Village, North Denpasar District, Denpasar City. In this study, researchers used a type of qualitative research with descriptive methods. The analysis uses theoretical indicators of the Policy Implementation model from George C. Edward III. The findings from the study indicate that the implementation of the Tegeh Sari Lestari Garbage Bank program has been going quite well, but there are several problems such as socialization that is still not effective, facilities and infrastructure that are still inadequate and the lack of participation of the surrounding community to take part in the Garbage Bank program. Recommendations that can be given are from the manager and the community who are members of the customer as a party involved in implementing the Tegeh Sari Lestari Garbage Bank program so that it can have a more positive impact on the environment.